2024
DOI: 10.3390/ani14030494
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Parainfluenza-3 Virus Detection Methods and Prevalence in Cattle: A Systematic Review and Meta-Analysis

Gebremeskel Mamu Werid,
Thien D. Van,
Darren Miller
et al.

Abstract: Bovine parainfluenza-3 virus (BPI3V) is an important respiratory pathogen in cattle, contributing to syndromes in the bovine respiratory disease complex (BRDC). Despite its significance, the understanding of its prevalence remains fragmented, especially within the larger framework of BRDC. This systematic review and meta-analysis aimed to determine the global prevalence of BPI3V in cattle using varied detection methods and to highlight associated risk factors. Of 2187 initially retrieved articles, 71 were sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 91 publications
0
0
0
Order By: Relevance
“…Furthermore, the BPIV3 genome was detected in 10.9% of nasal swabs in our study, aligning with previous research in Serbia, which reported a positivity rate of 6.7% using genome detection and virus isolation [21]. The average prevalence of BPIV3 in nasal swabs, as determined by PCR, was estimated at 7%, with age showing a significant influence but not farm type, which is consistent with our findings [22]. Considering the typical lack of control measures for BPIV3, even on large farms in Serbia, along with the virus's characteristics, such as efficient horizontal transmission, propensity for sub-clinical infections, and potential for reintroduction into herds [23], these results were anticipated.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the BPIV3 genome was detected in 10.9% of nasal swabs in our study, aligning with previous research in Serbia, which reported a positivity rate of 6.7% using genome detection and virus isolation [21]. The average prevalence of BPIV3 in nasal swabs, as determined by PCR, was estimated at 7%, with age showing a significant influence but not farm type, which is consistent with our findings [22]. Considering the typical lack of control measures for BPIV3, even on large farms in Serbia, along with the virus's characteristics, such as efficient horizontal transmission, propensity for sub-clinical infections, and potential for reintroduction into herds [23], these results were anticipated.…”
Section: Discussionsupporting
confidence: 92%